Human milk oligosaccharide 2′-fucosyllactose supplementation improves gut barrier function and signaling in the vagal afferent pathway in mice. Issue 18 (26th July 2021) - Lee, Sunhye; Goodson, Michael L.; Vang, Wendie; Rutkowsky, Jennifer; Kalanetra, Karen; Bhattacharya, Mrittika; Barile, Daniela; Raybould, Helen E.
Abstract : 2'-Fucosyllactose (2'-FL), a predominant human milk oligosaccharide, attenuates HF diet-induced metabolic and intestinal barrier impairment, improves gut hormone resistance, and alters the intestinal microbiota and microbiota-derived metabolites. Abstract : 2′-Fucosyllactose (2′-FL) is one of the predominant oligosaccharides found in human milk and has several well-established beneficial effects in the host. It has previously been shown that 2′-FL can improve the metabolic phenotype in high-fat (HF)-fed mice. Here we investigated whether dietary supplementation with 2′-FL was associated with improved intestinal barrier integrity, signaling in the vagal afferent pathway and cognitive function. Mice were fed either a low-fat (LF, 10% fat per kcal) or HF (45% fat per kcal) diet with or without supplementation of 2′-FL (10% w/w) in the diet for 8 weeks. Body weight, energy intake, fat and lean mass, intestinal permeability ( ex vivo in Ussing chambers), lipid profiles, gut microbiome and microbial metabolites, and cognitive functions were measured. Vagal afferent activity was measured via immunohistochemical detection of c-Fos protein in the brainstem in response to peripheral administration of cholecystokinin (CCK). 2′-FL significantly attenuated the HF-induced increase in fat mass and energy intake. 2′-FL significantly reduced intestinal permeability and significantly increased expression of interleukin (IL)-22, a cytokine known for its protective role in the intestine. Additionally, 2′-FL led to changes in the gut microbiota composition and in the associated microbial metabolites. Signaling in the vagal afferent pathway was improved but there was no effect on cognitive function. In conclusion, 2′-FL supplementation improved the metabolic profiles, gut barrier integrity, lipid metabolism and signaling in the vagal afferent pathway. These findings support the utility of 2′-FL in the control of gut barrier function and metabolic homeostasis under a metabolic challenge.